2014
DOI: 10.1111/jhn.12268
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and muscle strength throughout the life course: a review of epidemiological and intervention studies

Abstract: The putative role of vitamin D in muscle function and strength throughout the life course is of interest because muscle strength is required for engagement in physical activity at all ages. As vitamin D deficiency is widely reported in the population, especially in countries at high latitude, the potential importance of vitamin D in muscle function throughout life, and the potential impacts on growth and development, participation in physical activity, and effects on skeletal and cardio-metabolic health, compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Further clinical studies are needed in order to confirm this preliminary results. During aging, it has been registered a decline in 25(OH)vitamin D3 serum levels associated with reduced muscle mass, strength and performance in older adults (46,47). Moreover, a recent skeletal muscle gene expression study carried out in older adults (68-79 years) showed that lower expression of vitamin D receptor (VDR) was associated with higher lean mass (48).…”
Section: Other Mechanism Involved In Sarcopeniamentioning
confidence: 99%
“…Further clinical studies are needed in order to confirm this preliminary results. During aging, it has been registered a decline in 25(OH)vitamin D3 serum levels associated with reduced muscle mass, strength and performance in older adults (46,47). Moreover, a recent skeletal muscle gene expression study carried out in older adults (68-79 years) showed that lower expression of vitamin D receptor (VDR) was associated with higher lean mass (48).…”
Section: Other Mechanism Involved In Sarcopeniamentioning
confidence: 99%
“…Supplementation with calcifediol (20 µg over 6 months) improved appendicular lean mass, physical performance (Short Physical Performance Battery), 4-m gait speed, and reduced mean number of falls in post-menopausal women (aged 68 years) who were diagnosed with osteoporosis or had 25(OH)D concentration <75 nmol/L [18]. Lastly, results from observational studies [3,19], although inconsistent, have suggested that a 25(OH)D concentration of <50 nmol/L exerts a negative effect on various measures of muscle strength and function and physical performance in older adults aged ≥60.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of calcium in muscle contraction and the ease with which myopathy in osteomalacia is reversed with vitamin D therapy indicates possible role of vitamin D on skeletal muscle strength. Most of the randomized control trials (RCTs) have been in elderly subjects and showed variable effects of vitamin D supplementation on muscle strength . Factors which might explain this variability are (i) wide age range, 50 years to centenarians, (ii) differences in baseline serum 25(OH)D, sufficient to deficient, (iii) absence of calcium supplementation (iv) lack of stratified analysis accounting interindividual differences in sex hormone and (v) presence of sarcopenia.…”
Section: Introductionmentioning
confidence: 99%